Protein supplementation preserves muscle mass in persons against sleeve gastrectomy - Afsar, Nagehan; Ozdogan, Yahya (Frontiers in Nutrition, 2024)
Sleeve gastrectomy surgery can lead to deficiencies in both macro and micronutrients, with protein being particularly crucial due to its role in muscle mass, physiological, and metabolic functions. Inadequate protein intake due to physiological, psychological, or financial reasons may prevent achieving the recommended intake levels. The significance of this issue is often underappreciated.Aim: This study evaluates the impact of protein supplementation on muscle mass in individuals undergoing sleeve gastrectomy and emphasizes the need for more comprehensive dietary training by expert dietitians.Method: Data were collected from 60 participants (15 male, 45 female, aged 20-54) who visited the surgery clinic. Participants were divided into two groups: those receiving the recommended protein supplement (15g/day) with post-bariatric surgery diet training (BSD+PS), and those receiving only the post-bariatric surgery diet (BSD). A pre-surgery questionnaire gathered health and general information. Daily energy and nutrient intakes were recorded using 24-hour food consumption logs on the day before surgery and at 7 days, 1 month, and 3 months postoperatively. Anthropometric measurements, including muscle and fat mass, and International Physical Activity Questionnaire (IPAQ) data were also collected.The characteristics of participants in both groups were similar, although there were more females in the BSD+PS group (86.7%) compared to the BSD group (63.3%). Despite an increase in energy and nutrient intake over time, levels remained below the recommended amounts in both groups. A significant difference was found in protein supplement consumption between the groups (p = 0.000). Repeated measures showed significant differences in body muscle mass percentage over time (F=202.784; p=0.000). In individuals who underwent sleeve gastrectomy surgery, deficiencies in macro and micronutrient intake were observed below reference levels. For this reason, the first approach in the treatment of obesity should always be medical nutrition therapy accompanied by a dietician. When designing post-bariatric surgery nutrition programmes, it should be taken into consideration that nutrition protocols and trainings should be followed more closely and given in more detail under the supervision of a specialist before supplements are considered.